The work and the reader in literary studies - Eggert, Paul (Cambridge University Press, 2020)
By the late 1980s the concept of the work had slipped out of sight, consigned to its last refuge in the library catalogue as concepts of discourse and text took its place. Scholarly editors, who depended on it, found no grounding in literary theory for their practice. But fundamental ideas do not go away, and the work is proving to be one of them. New interest in the activity of the reader in the work has broadened the concept, extending it historically and sweeping away its once-supposed aesthetic objecthood. Concurrently, the advent of digital scholarly editions is recasting the editorial endeavour. The Work and The Reader in Literary Studies tests its argument against a range of book-historically inflected case-studies from Hamlet editions to Romantic poetry archives to the writing practices of Joseph Conrad and D. H. Lawrence. It newly justifies the practice of close reading in the digital age.
Title from publisher's bibliographic system (viewed on 26 Aug 2019)
Keywords: Werk; Edition; Textgeschichte; Kritische Ausgabe; Digitale Edition